Adventitious Plants and Cultivated Plants in Greenland. - Pedersen, Anfred (Meddelelser om Grønland, 1972)
This paper can be considered as a supplement to M. P. PORSILD (1932): Alien Plants and Apophytes of Greenland, Meddelelser om Grønland Bd. 92 Nr. 1. Chapter I gives information concerning all known finds of adventitious plants in Greenland in the period 1810- 1970. In this chapter finds of non-naturalized occurrences are set in 6 point type. The distribution of the majority of the naturalized species is shown figures 3-40 (pp. 67-72). OSTENFELD (1926) and M. P. PORSILD (1932) discussed the question of which species can be assumed to have been accidentially introduced to Greenland from Iceland and Norway in the Norse period from ca. 985 to the 1400’s; this is touched upon here. There are references to finds of seeds and fruit that were found in cultural layers dating from the Norse period (IVERSEN, 1953; FREDSKILD, 1969). The following introduced species are believed to have survived from the 1400’s to 1721, when there were no European peoples in Greenland: Achillea millefolium, Leontodon autumnalis var. taraxaci, Tripleurospermum maritimum ssp. boreale, Vicia cracca, and Rumex longifolius. It also is probable that Agrostis stolonifera, Potentilla anserina s. str., Stellaria media, and Polygonum boreale survived throughout this period, Elymus arenarius s. str. maybe. Chapter II deals with some species or subspecies that are regarded as indigenous in Greenland, i.a. , Anthoxanthum odoratum, Atriplex longipes, Cakile edentula, Cirsium heterophyllum, Elymus arenarius s. str., Galium boreale, Puccinellia maritima, Ranunculus cymbalaria, Rorippa islandica s. str., Rubus saxatilis, Tripleurospermum maritimum ssp. phaeocephalum, and Zostera marina. According to other authors they are all regarded as accidentally introduced. Chapter I, page 66, mentions some species that are believed to be both indigenous and accidentally introduced plants. Chapter III gives a survey of plants that are cultivated in Greenland, or whose cultivation has been attempted there.